2010
DOI: 10.1007/s11085-010-9225-3
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Scale Depletion and Enrichment Processes During High Temperature Oxidation of the Nickel Base Alloy 625 in the Temperature Range 900–1000 °C

Abstract: Numerous chromia-forming austenitic steels and nickel-base alloys contain chromium-rich strengthening precipitates, e.g. chromium-base carbides. During high temperature exposure the formation of the chromia base oxide scale results in chromium depletion in the alloy matrix and consequently in dissolution of the strengthening phase in the sub-surface zone. The present study describes the oxidation induced phase changes in the chromium depletion layer in case of alloy 625, a nickel base alloy in which the streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 122 publications
(64 citation statements)
references
References 43 publications
(45 reference statements)
12
52
0
Order By: Relevance
“…A final feature of note in this region is the strong Nb enrichment directly beneath the oxide scale. Similar enrichment has also been documented in previous experimental and thermodynamic modelling studies on oxidised Inconel 625 and 718 alloys [8,[25][26][27]. Chyrkin et al [8] reported the formation of a localised d phase within the denuded zone beneath the oxide scale, not seen in the bulk.…”
Section: Discussion Oxidation Conditionssupporting
confidence: 80%
See 4 more Smart Citations
“…A final feature of note in this region is the strong Nb enrichment directly beneath the oxide scale. Similar enrichment has also been documented in previous experimental and thermodynamic modelling studies on oxidised Inconel 625 and 718 alloys [8,[25][26][27]. Chyrkin et al [8] reported the formation of a localised d phase within the denuded zone beneath the oxide scale, not seen in the bulk.…”
Section: Discussion Oxidation Conditionssupporting
confidence: 80%
“…The enrichment of Si near/inside the oxide scale should also be noted, consistent with the EPMA data of Fig. 2 and prior spectroscopic measurements [8].…”
Section: Exhaust Contaminantssupporting
confidence: 89%
See 3 more Smart Citations